Fiscal rules migate economic setbacks during crises - Alexander Kriwoluzky; Laura Pagenhardt; Malte Rieth (DIW Weekly Report, 2020)
91 countries around the world have established fiscal rules to limit national debt and/or budget deficits. Using data from previous natural disasters, this report investigates how these fiscal rules affect overall economic development following a crisis. The results show countries with fiscal rules fare better after such shocks than those without. GDP, private consumption, and investments develop markedly and sustainedly better: They are two to four percent higher and growth lasts for two to four years. The key factor here is likely fiscal policy, which can be expansionary, particularly if the fiscal rules pro-vide for exceptions. This is in adherence with the idea that the rules create fiscal space in good times that can later be used in bad times. For example, during the coronavirus pandemic, the German debt break has proven its worth. However, to be prepared for future crises, it must be re-implemented in a timely manner.
Keywords: E62; C32; E32; H50; 330; Fiscal policy; world economy; fiscal regimes; panel data; natural disasters